2022
DOI: 10.55251/jmbfs.5725
|View full text |Cite
|
Sign up to set email alerts
|

Date Palm Phoenix Dactilifera L. Seed Oil: Variety Effects on Physicochemical Characteristics, Fatty Acid Composition, Sterol and Tocol Contents

Abstract: The date palm (Phoenix dactylifera L.) grows in the world's arid and semi-arid regions, particularly in the majority of Middle Eastern countries. It has played an important role in the survival of many ancient civilizations. It is regarded as a valuable nutrient, but it also plays an important role in the economies of date-producing countries. Date palm seeds are commonly described as waste after consuming their pulp by industries or individuals. However, date pits contain a valuable source of edible oil chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…antioxidant, anti-inflammatory, and anticarcinogenic activities, in addition to estrogenic and aphrodisiac activities. [10,26] A recent study by Halabi et al [27] reported that date seed oil contains sterols as much as other seed oils, for instance rapeseed and soybean with β-sitosterol being the most predominant sterol among the studied varieties. It is important to emphasize that the high contents of phytosterols in date pollen grains accounted for their fertility promoting characteristics [9] (Table 1 and Figure 4).…”
Section: Phytosterolsmentioning
confidence: 98%
See 2 more Smart Citations
“…antioxidant, anti-inflammatory, and anticarcinogenic activities, in addition to estrogenic and aphrodisiac activities. [10,26] A recent study by Halabi et al [27] reported that date seed oil contains sterols as much as other seed oils, for instance rapeseed and soybean with β-sitosterol being the most predominant sterol among the studied varieties. It is important to emphasize that the high contents of phytosterols in date pollen grains accounted for their fertility promoting characteristics [9] (Table 1 and Figure 4).…”
Section: Phytosterolsmentioning
confidence: 98%
“…[1] Oleic acid was also reported to be the major unsaturated fatty acid (52.60 % -42.13 %) in P. dactylifera date seed oil. [26] The fatty acid content of the seed oil other species belonging to the Arecaceae family was studied comprehensively revealing its characterization with high contents of lauric and myristic acids of (16-52 %) and (7-51 %), respectively. P. rupicola seed oil was reported to contain the unsaturated fatty acids; oleic and linoleic (41.2 % and 10.6 %, respectively), in addition to the saturated fatty acids lauric and myristic (20.8 % and 12.4 %, respectively) and displayed in vitro estrogenic activity on MCF7 cell lines.…”
Section: Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher the extinction, the richer the oil is in oxidation products, and the less stable it is. Measurement of these specific extinction coefficients is suitable for determining oil quality [25]. The extinction coefficients K 232 and K 270 nm decreased significantly for the activated carbon process.…”
Section: Evaluation Of the Effect Of Processing On The Chemical Chara...mentioning
confidence: 99%
“…Date seed can produce highquality oil for cosmetic and pharmaceutical applications (Alahyane et al, 2022). The date palm is also used as an ornamental plant in gardens and resorts (Halabi et al, 2023). Furthermore, researches have shown that date palms require specific climatic conditions and well-drained soils for successful fruit production (Jiddeine et al, 2022).…”
Section: Introductionmentioning
confidence: 99%